Kadar Protein Plasma Darah Tikus Putih (Rattus norvegicus) Bunting yang Mengkonsumsi MSG Organik dan MSG Sintetis - Sagita, Ninit Putry; Setyaningsih, Endang; Febrianti, Ulya Ananda Putri; Fauziah, Daniar Eka Nur; Febriyanti, Amalia; Ariyanti, Firma; Tyas, Eriza Putri Ayu Ning; Wicaksono, M. Galih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the levels of blood plasma protein in pregnant white rats (Rattus nervagicus) that consume Organic MSG and Synthetic MSG. This research method is experimental using a Completely Randomized Design (CRD) by random sampling 21 pregnant white rats with 3 replications and 7 treatments consisting of positive control treatments, P1 = 0.5 ml Organic MSG, P2 = 1 ml Organic MSG, P3 = 2 ml Organic MSG, P4 = 0.5 ml Synthetic MSG, P5 = 1 ml Synthetic MSG, P6 = 2 ml Synthetic MSG for 19 days. The variables measured were blood plasma protein levels measured using a refractometer with units of g / dL. The data tested using SPSS analysis with one way ANNOVA test then continued with Duncan's Multiple Range Test (DMRT). The results showed that Organic MSG had a positive effect on blood plasma protein levels which were significant to the difference in blood plasma protein levels. This can be implied in the health of pregnant rats if there is MSG that enters it will provide viscosity to the blood so that blood plasma protein will be high working hard to produce white blood cells to balance red blood cells that affect immunity. The blood plasma protein levels of pregnant white rats given liquid Organic MSG were the highest at 13.562 g/dL and the lowest at 13.55 g/dL.